2023
DOI: 10.1021/acssuschemeng.2c05369
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Water and Methanol with Zeolites for Heat Transfer

Abstract: Reducing carbon dioxide emissions has become a must in society, making it crucial to find alternatives to supply the energy demand. Adsorption-based cooling and heating technologies are receiving attention for thermal energy storage applications. In this paper, we study the adsorption of polar working fluids in hydrophobic and hydrophilic zeolites by means of experimental quasi-equilibrated temperature-programmed desorption and adsorption combined with Monte Carlo simulations. We measured and computed water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 90 publications
3
10
0
Order By: Relevance
“…At the other end of the spectrum, ZIF-8 demonstrates the most modest storage densities, failing to breach the 200 kJ/kg threshold for both R125 and R170. Significantly, in the studied conditions, MIL-101’s storage densities for the R125 refrigerant resemble those observed in methanol adsorption within zeolites such as NaY or NaX, as well as methanol and ethanol within activated carbons. , It is worth mentioning that well-established pairs containing water and zeolites (NaY, NaX, and CaX) outperform the storage densities obtained here, with values ranging from 700 to 880 kJ/kg. However, high temperature (above 450 K) and low pressures are needed in order to achieve these values. ,, While those extreme conditions can be within the range of operational temperatures and pressures of some industrial processes, they can be difficult to obtain for other processes working near ambient conditions.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…At the other end of the spectrum, ZIF-8 demonstrates the most modest storage densities, failing to breach the 200 kJ/kg threshold for both R125 and R170. Significantly, in the studied conditions, MIL-101’s storage densities for the R125 refrigerant resemble those observed in methanol adsorption within zeolites such as NaY or NaX, as well as methanol and ethanol within activated carbons. , It is worth mentioning that well-established pairs containing water and zeolites (NaY, NaX, and CaX) outperform the storage densities obtained here, with values ranging from 700 to 880 kJ/kg. However, high temperature (above 450 K) and low pressures are needed in order to achieve these values. ,, While those extreme conditions can be within the range of operational temperatures and pressures of some industrial processes, they can be difficult to obtain for other processes working near ambient conditions.…”
Section: Resultssupporting
confidence: 61%
“…Through this property, we can estimate the amount of heat released or required during adsorption/desorption cycles. This is so-called the thermochemical storage density (SD), which is calculated by the integration of the isosteric enthalpy of adsorption (Δ h ( q )) between adsorption and desorption conditions: SD = prefix∫ q a d s q d e s normalΔ h ( q ) d q To obtain the release capacity under varying conditions and to integrate eq , it is convenient to employ smooth functions for the adsorption isotherms and enthalpy of adsorption curves. The latter was interpolated using cubic splines.…”
Section: Methodsmentioning
confidence: 99%
“…The DP theory has been questioned because it is based on the postulate that the mechanism for adsorption in micropores is that of pore filling rather than layer-by-layer formation of a film on the walls of the pores, which may describe the adsorbate with fixed characteristic energy and lead to a value of enthalpy of adsorption close to the enthalpy of vaporization of the fluid. In previous studies, we have used this theory to calculate the enthalpy of adsorption of (i) light alcohols in activated carbons with functional groups acting as strong interaction sites for adsorption, 56 (ii) of methanol and water in aluminosilicates by changing the Si/Al ratio giving rise to hydrophilic and hydrophobic adsorbents, 37 and (iii) for water in mesoporous carbons. 96 In these studies, we have demonstrated that the predicted enthalpy of adsorption agrees with the experimental value.…”
Section: Methodsmentioning
confidence: 99%
“…94 This formulation has been extensively used in the literature for the study of porous adsorbents for energy storage applications. 37,56,89,90,95 The enthalpy of adsorption can be calculated using the enthalpy of vaporization, the adsorption potential, which is the molar free energy of adsorption with opposite sign, and the entropy variation:…”
Section: Thermodynamic Modelmentioning
confidence: 99%
See 1 more Smart Citation